Multimedia and interactive innovation in Argentinean online journalism - Vázquez-Herrero, Jorge (2019)
Argentinean online media have followed international trends in their digital trajectory and they have taken on the constant changes in the media ecosystem by innovating with the production of multimedia and interactive formats designed for the Internet, as well as technological initiatives such as virtual reality. From the organizational point of view, the convergence of newsrooms and the creation of labs are some of the identified features. In this article, a case study of La Nación, La Capital, La Voz del Interior and Clarín is developed, identifying its innovative elements and interviewing digital professionals. At a global level, the media of Argentina show an innovative nature, although unstable. The search for a sustainable model, the provision of economic, technological and human resources for the digital area and a strategic commitment of companies can provide what is necessary to ensure their consolidation in the network.